Some Innovations in the Law on General Administrative Procedure “Administrative Proceeding” - Milkov, Dragan; Radošević, Ratko S. (Zbornik radova Pravnog fakulteta u Novom Sadu, 2017)
Abstract: In 2016 the Republic of Serbia passed the new Law on general administrative procedure. However, the new Law regulates not only procedural, but also substantive institutions. In this paper the authors analyze the problems of this inappropriate way of legal regulation. The Analyze shows that these substantive institutions are created artificially. As a result there are vague and imprecise criteria for their definition and delimitation, as well as numerous contradictions. Keywords: administrative procedure, administrative matter, administrative act, guarantee act, administrative contract, administrative actions, provision of public services.